Identification of the key urban facilities management principles of a sustainable urban precinct: A case study of Ebene Cybercity, Mauritius - Boodhun, Hanna (Department of Construction Economics and Management, 2017)
Purpose - The aim of this thesis documentation was to identify the Urban FM principles and key criteria which contribute to the attainment of a sustainable urban precinct. The need for a better understanding of the relationship between buildings, people and the urban precinct to facilitate the development of an increased understanding of sustainable cities was highlighted during the literature review. Urban FM, as an emerging field, also created the need for the study of FM principles at a macro scale. Design/methodology/approach - Using the case study methodology, the research used the case of Ebene Cybercity and adopted a social constructionist, interpretivist framework. Qualitative data was collected using face-to-face interviews as the prime data collection technique and analysed through generation of themes. Findings - The main findings were that FM principles at a macro scale are mainly applied at a strategic level and as such, implementation of an FM plan needs a strategic awareness and support at the top level of the structure being managed; involving both the political leadership and the top management of the urban precinct. It was also found that implementation of such an FM strategy at the macro scale was allowed through the following key criteria: a clustering effect, flexibility, formal communication channels, design preconditions and macro strategic drivers. These findings were thus used as a basis for the generation of a model to establish the principles of a macro urban FM strategy and a list of key criteria which facilitate the implementation of such a strategy. Practical Implications - The thesis finally ends with the proposition for further research in the field of Urban FM at a macro level to strengthen the generalisation to theory and work towards a new infrastructure model firmly anchored in the sustainability principles. The scope for future research in the African context with its low level of urbanisation is particularly relevant where there is need for new, wide-ranging urban policies to create African cities and towns capable of generating sustainable growth and development.